The Effect of Construction Joints on the Behavior of Reinforced Concrete Deep Beams - Kadhum, Saba Basim; Al-Zuhairi, Alaa Hussein (Engineering, Technology & Applied Science Research, 2024)
The main objective of the present research is to conduct a thorough investigation into the impact of construction joints on the structural performance of reinforced concrete deep beams. This study involves a series of experimental tests and the use of advanced numerical analysis techniques to gain a deeper understanding of the behavior of these beams in the presence of construction joints. The experimental component incorporates analysis findings from both previous and current research. Specifically, six reinforced concrete deep beam specimens featuring horizontal and inclined construction joints were utilized as simply being supported with two-point loading. The test findings indicate that the presence of a horizontal construction joint located below, at, or above the mid-height of the beam can lead to reductions in the ultimate load capacity by 9%, 11%, and 1%, respectively. The numerical part of the study focused on creating detailed models of the deep beam specimens with construction joints using the ABAQUS software. The proposed model showed a good agreement with the experimental tests, with estimations not exceeding 7% for the load-carrying capacity. This reduction becomes more significant when the concrete compressive strength is high, necessitating the use of bonding agents and additional reinforcement techniques to mitigate the impact of construction joints on the structural integrity.